ISO 31000 Risk Management Maturity in Indonesian BUMN: A Qualitative Document Analysis in the Context of the Danantara Governance Reform - Osly Usman; Adnan Kasofi; Ryna Parlyna (Fundamental and Applied Management Journal, 2026)
This study proposes and applies the ISO 31000 Assessment Index (I31-AI), the first 35-indicator tiered scoring tool specifically calibrated to the PER-5/2022 four-tier BUMN classification to measure ISO 31000:2018 risk management maturity across the seven operative dimensions of the standard. The study used an interpretative qualitative design that combined systematic document analysis of regulatory texts with thematic coding of 41 active BUMN annual reports and supervisory records for FY2022-2024. Each BUMN was scored on all 35 I31-AI indicators on a CMMI-adapted 0-4 maturity scale; inter-rater reliability was verified at Cohen’s Kappa k = 0.81. Cross-tier pattern synthesis was completed using reflexive thematic analysis (Braun & Clarke, 2021). Five dominant themes emerge: (1) coercive regulatory pressure yields structural compliance but does not build risk culture (P5) or dynamic review (P6); (2) a distinct tier gradient is observed in maturity scores, with Sistemik A’s average score of 84.4 and Netral’s of 46.8; (3) the construction sector is a concentrated portfolio risk cluster for Danantara, with five Signiﬁkan-tier BUMN falling below the Netral threshold; (4) P5 and P6 have the largest cross-tier deﬁcits, at 39.3 and 39.0 points respectively; and (5) I31-AI scores act as forward-looking ﬁscal risk signals, with all seven BUMN in ﬁnancial distress identiﬁed by Kementerian BUMN (2024) scoring below their tier-appropriate thresholds. The I31-AI is the first scoring tool explicitly calibrated to the PER-5/2022 four-tier classification and validated against publicly available governance evidence. It provides BP BUMN with a structured basis for shifting supervisory focus from structural conformance to P5/P6 capability development, and gives Danantara a portfolio-level fiscal risk signal complementary to financial performance indicators.